Urban river design and aesthetics: a river restoration case study from the UK. Issue 4 (3rd July 2016) - Prior, Jonathan
Abstract: This paper analyses the restoration of an urbanized section of the River Skerne where it flows through a suburb of Darlington, England; a project which was one of the first comprehensive urban river restorations undertaken in the UK. It is shown how aesthetic values were central to the identification of the River Skerne as a site for restoration, the production of restoration objectives, and a design vision of urban river renewal via restoration. Secondly, the means by which these aesthetic values were realized through the design and implementation of restoration techniques and management operations are described. Finally, it is demonstrated how the resulting aesthetic qualities and overall landscape character were intended to accomplish a set of interrelated policy goals.